2015
DOI: 10.4161/2162402x.2014.991613
|View full text |Cite
|
Sign up to set email alerts
|

Human NK cells activated by EBV+lymphoblastoid cells overcome anti-apoptotic mechanisms of drug resistance in haematological cancer cells

Abstract: Natural killer (NK) cells recognize and eliminate transformed or infected cells that have downregulated MHC class-I and express specific activating ligands. Recent evidence indicates that allogeneic NK cells are useful to eliminate haematological cancer cells independently of MHC-I expression. However, it is unclear if transformed cells expressing mutations that confer anti-apoptotic properties and chemoresistance will be susceptible to NK cells. Allogeneic primary human NK cells were activated using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 55 publications
10
46
0
Order By: Relevance
“…Cell death was almost completely inhibited by EGTA indicating the granule exocytosis was the main mechanism employed by NK cells to kill B-CLL cells (data not shown). As previously found in NK cells activated with R69 LCLs (51), the NK cell receptors NKG2A, NKp30, NKp44, and DNAM and the cytotoxic protease granzyme B were upregulated in activated NK cells (data not shown).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Cell death was almost completely inhibited by EGTA indicating the granule exocytosis was the main mechanism employed by NK cells to kill B-CLL cells (data not shown). As previously found in NK cells activated with R69 LCLs (51), the NK cell receptors NKG2A, NKp30, NKp44, and DNAM and the cytotoxic protease granzyme B were upregulated in activated NK cells (data not shown).…”
Section: Resultssupporting
confidence: 81%
“…Our group has previously described that NK cells activated with EBV-transformed R69 or 721.211 LCLs are able to eliminate cells from B-CLL patients without requiring supplementation with exogenous cytokines (51). Importantly, activated NK cells did not kill healthy non-transformed PBMCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that Tc cells use PRF1 and GZMB to kill cells in which both the intrinsic mitochondrial pathway and caspases are blocked (93), highlighting the potential benefits of immunotherapy to treat cancer cells that do not respond to conventional therapy (3,4). We have recently confirmed in humans that allogeneic activated NK cells expressing GZMB eliminate hematologic cancer cells in which apoptosis is blocked by p53 mutation and overexpression of Bcl-x L or downregulation of Bak and Bax even in the presence of caspase inhibitors (99). However, under these circumstances, the phenotype of dying cells is not apoptotic, and PS translocation did not preceded membrane permeability.…”
Section: Who Makes What During Cell Death Induced By Cls?mentioning
confidence: 50%